Intradural symptomatic arachnoid cyst formation following non-instrumented lumbar decompression. (4th May 2021) - Yuen, Jason; McGavin, Lucy; Adams, Will; Haden, Nicholas
Abstract: Purpose: Intradural arachnoid cyst is a rare complication of lumbar puncture, post-trauma or post-intraoperative durotomies. We aim to estimate the incidence of early intradural arachnoid cyst radiologically in non-instrumented posterior lumbar decompression among symptomatic patients, and establish clinical correlation. Materials and methods: Patients who underwent lumbar decompression without instrumentation at a tertiary spinal service between December 2014 and January 2018 were identified. When MRI scans were performed post-operatively within 14 days, imaging, medical and operative records were reviewed by two consultant neuroradiologists. Results: 488 operations were included. 46 operations were followed by an early MRI scan. 59% were requested to investigate new or ongoing pain. Ten demonstrated an intradural arachnoid cyst – seven had no documented durotomy. Eight were primary operations, three were emergency operations. Statistically, we have not identified durotomy, primary-vs-revision surgery, and elective-vs-emergency surgery as risk factors. Two patients required revision operations, of these, one had a repeat post-operative scan, where the cyst resolved following further decompression at the index level, without intradural exploration. Conclusions: Intradural arachnoid cyst may complicate posterior lumbar decompression. To our knowledge, this is the first study to assess its incidence as an early post-operative radiological finding, which is likely to be commoner than we recognise. It may be a cause of persisting post-operative pain.